Essential oil from Euphorbia esula inhibits proliferation and induces apoptosis in HepG2 cells via mitochondrial dysfunction (Brazilian Journal of Pharmaceutical Sciences, 2020)
Hepatocellular carcinoma is one of the most prevalent malignancies and a leading cause of cancer-related mortality worldwide. However, the therapies to prevent hepatocellular carcinoma are still limited and the emergence of drug resistance leads to the development of new anti-cancer drugs and combinational chemotherapy regimens. Our study was aimed to explore the anticancer effects of the essential oil extract (EEEO) from Euphorbia esula which has been widely used in traditional Chinese folk medicine and possessed potential cytotoxic effects in several human tumor cells. However, the mechanisms of EEEOinduced anti-proliferation and apoptosis have not been completely elucidated. In this study, EEEO was prepared by hydro-distillation and the main chemical component of EEEO was identified by GC-MS. HepG2 cells were treated with EEEO in vitro and then evaluated with respect to proliferation, apoptosis, and levels of reactive oxygen species (ROS) and apoptotic proteins. Our studies showed that EEEO decreased cell viability, elevated ROS levels, and induced apoptosis of HepG2 cells in a concentrationand time-dependent manner. Furthermore, Bcl-2 was down-regulated, while Bax was up-regulated in HepG2 after EEEO treatment. These results suggest that EEEO induced apoptosis of HepG2 cells and indicate that this apoptosis might be mediated by the mitochondrial pathway.